2020
DOI: 10.3390/w12010147
|View full text |Cite
|
Sign up to set email alerts
|

Household Water Security: An Analysis of Water Affect in the Context of Hydraulic Fracturing in West Virginia, Appalachia

Abstract: Hydraulic fracturing has been booming in the last decade in the United States. While natural gas extraction and production has improved the national energy security, it has raised questions around the water security of those communities where extraction is taking place. Both scientists and residents are concerned about hydraulic fracturing’s impacts on surface- and groundwater, especially regarding how hydraulic fracturing impacts residents’ access to safe household well water. In the past decade, the Marcellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…In addition, participant self-reported housing damage has shown strong correlation with cumulative ground motion assessed from shakemaps (i.e., visual displays of ground shaking occurring at different locations immediately after an earthquake). In terms of UOGD, residents have also reported on observable changes to their air or water, such as odors, change in the color, appearance, turbidity, or foaming of their drinking water [ 16 , 30 , 78 ].…”
Section: Survey Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, participant self-reported housing damage has shown strong correlation with cumulative ground motion assessed from shakemaps (i.e., visual displays of ground shaking occurring at different locations immediately after an earthquake). In terms of UOGD, residents have also reported on observable changes to their air or water, such as odors, change in the color, appearance, turbidity, or foaming of their drinking water [ 16 , 30 , 78 ].…”
Section: Survey Methodsmentioning
confidence: 99%
“…With more than 9 million people in the USA relying on drinking-water sources located within 1.6 km (1 mile) from a UOG well [ 9 ], water contamination from UOGD has been a major community concern [ 15 , 16 ]. Hundreds of chemicals have been reportedly used in injection water or detected in wastewater, including known and suspected endocrine disruptors and carcinogens, such as metals, volatile organic compounds, polycyclic aromatic hydrocarbons, phthalates, and per- and poly-fluoroalkyl substances (PFAS) [ 9 , 17 23 ].…”
Section: Uog-related Stressorsmentioning
confidence: 99%
“…All cumulative 90 interviews -ranging from 45 to 90 minutes -were transcribed and analyzed in the qualitative data software NVivo. For this paper, we focus on the codes of 'land,' 'landscape,' 'erosion,' 'home,' 'rural,' and 'livelihood' (for additional studies see Brock Carlson & Caretta, in print; Turley & Caretta, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…With the quick appearance of industrial and extractive infrastructure, participants stressed that their sense of security, embodied in their homes and peaceful surroundings, had disappeared just as quickly. In addition to the sights and sounds of industrial development combined with dramatic changes in the landscape, participants reported that they were unsettled by the possibility of pollution, water contamination, and even explosions due to this infrastructure near their property (see also Turley & Caretta, 2020).…”
Section: From Rural Idyll To Despairmentioning
confidence: 99%
“…The theme of disempowerment at the hands of technocracy evoked above by Aijaz and Akhter (2020), takes center stage in Turley and Caretta's (2020) [7] account of household water security in the context of hydraulic fracturing in West Virginia, Appalachia in the United States. Weaving their account around the concept of water security as time and place specific and constituting the three essential dimensions of water access, quality and affect, i.e., emotional, cultural and subjective experience of water, Turley and Caretta (2020) focus in on how drinking water quality concerns around hydro-fracking in West Virginia intersect with water affect.…”
Section: Contributionsmentioning
confidence: 99%